Clinical, epidemiological and therapeutic profile of patients with brachioradial pruritus in a reference service in dermatology - Pinto, Ana Cecília Versiani Duarte; Wachholz, Patrick Alexander [UNESP]; Masuda, Paula Yoshiko; Martelli, Antonio Carlos Ceribelli (FapUNIFESP (SciELO), 2016)
This is a cross-sectional study, conducted from May to November/2014, in a dermatology reference unit, through review of medical records and interviews. In a sample of 49 patients with brachioradial pruritus, we observed higher prevalence of Caucasian (81.6%) and women (73.5 %), with a mean age of 56.1 years. Pruritus occurred in the topography of brachioradialis muscle in 87.8% of cases; 59.2% of the sample reported worsening of pruritus with sun exposure; the mean intensity of this symptom before treatment was 8.63. Therapy effectiveness was described as “very good/good” in 79.2% of cases, and for 55.3% relapses were categorized as “uncommon”.
Keywords: Case studies; Descriptive; Epidemiology; Pruritus; Skin diseases; Skin manifestations